SYSTEMATIC LITERATURE REVIEW ON COMMUNICATION IN CONSTRUCTION PROJECT MANAGEMENT: ISSUES AMONG PROJECT PARTICIPANTS - Norazlin Abd Aziz; Faizul Azli Mohd Rahim; Nur Mardhiyah Aziz (Journal of Surveying, Construction and Property, 2022)
Project communication is an important aspect that needs to be stressed in project management to ensure good project delivery in the construction industry. All the key players in construction must represent a good communication flow among themselves to avoid misunderstanding that later will affect their performance and reputation. However, there are still have issues among themselves while communicating. These communication issues are not only happening in Malaysia but in many other developing countries that are involved in the construction industry. However, there are insufficient studies on these communication issues involving project participants. Hence, the present article employs a systematic literature review to determine the issues of communication among project participants in the construction industry. The study was combined many research designs and the review was referring to ROSES (Reporting Standards for Systematic Evidence Syntheses) protocols. This research employs a systematic literature review of selected published indexed journals from Web of Science and Scopus. The findings identified several communication issues that can be categorized into different themes, which are; (1) accuracies, (2) timeliness, (3) distortions, (4) barriers, (5) under loading, (6) overloading, (7) misunderstanding, (8) gatekeeping, (9) procedures, and lastly (10) financial. Furthermore, the study also presented several significant contributions for practical purposes and a body of knowledge. The findings also described the importance of good strategies to overcome the communication issues and to look at the potential impact of those solutions on the whole progress of the projects.